Injury Risk Factors Associated With Weight Training. Issue 2 (February 2022) - Grier, Tyson; Brooks, Raina D.; Solomon, Zack; Jones, Bruce H.
Abstract : Abstract: Grier, T, Brooks, RD, Solomon, Z, and Jones, BH. Injury risk factors associated with weight training. J Strength Cond Res 36(2): e24–e30, 2022—The purpose of this evaluation was to identify injury risk factors associated with weight training (WT). Subjects were 4, 785 men and 542 women in a U.S. Army Division. Personal characteristics, unit training, personal training, fitness, and 12-month injury history were obtained by an electronic survey. Risk factors for WT injuries were explored using backward stepping multivariable logistic regression. Risk ratios, odds ratios (ORs), and 95% confidence intervals (95% CIs) were calculated for each risk factor. Over a one-year period, 4.5% of men and 0.6% of women experienced a WT injury. Weight-training injury incidence was 0.31 and 0.05 per 1, 000 hours of WT for men and women, respectively. Overall, men were 7.4 times more likely to experience a WT injury compared with women. For men who participated in WT, independent risk factors for a WT injury included older age (OR [23–27/⩽ 22 years] = 1.99, 95% CI 1.22–3.27; OR [>28/⩽ 22 years] = 2.48, 95% CI 1.52–4.03) and higher amounts of personal WT per week (OR [60–165/≥ 166 minutes] = 0.58, 95% CI 0.39–0.88; and OR [15–59/≥ 166 minutes] = 0.40, 95% CI 0.24–0.66). A linear trend was revealed indicating an increasing risk of a WT injury with greater amounts of time spent WT per week ( p < 0.01). Performing moderate amounts of WT may reduce the risk of experiencing a WT injury. However, because muscle strength is an important component of fitness for Soldiers, specialized WT programs that improve strength while minimizing injury risks are needed.